Effects of relative drop heights of drop jump biomechanics in male volleyball players - Peng, H.-T.; Song, C.-Y.; Wallace, B. J.; Kernozek, T. W.; Wang, M.-H.; Wang, Y.-H. (International Journal of Sports Medicine, 2019)
Previous cross-sectional studies have reported that higher drop heights do not always result in improved performance, and may increase injury risk during drop jumps (DJ). The purpose of this study was to analyze the kinematics and kinetics during the DJ in order to determine the relative drop height that maximize performance without exposing the lower extremity joints to unnecessary loads. Twenty male Division I college volleyball players volunteered. Data were collected using 11 infrared cameras and two force platforms. Participants performed three maximal effort countermovement jumps (CMJ). Subsequently, 50, 75, 100, 125, and 150% CMJ height (CMJH) was used to scale their relative drop height for three DJ trials per height. There was a significant increase in the landing phase impulse when the drop height exceeded 100%CMJH (p<0.05). At 125% and 150%CMJH, the negative work of knee and ankle significantly increased. The incoming velocity, kinetic energy, landing depth, maximum ground reaction force, landing impulse and power absorption of knee and ankle all increased with drop height (p<0.05). DJ height and reactive strength index following the drop landing were not statistically different between any of the drop heights (p>0.05). 50% to 100%CMJH may be the appropriate individual relative drop height for the DJ.